Oxygen isotope ratios of planktonic and benthic foraminifera collected from marine sediment core KR05-15_PC01 and KR05-15_PL01 - Kubota, Kaoru; Yokoyama, Yusuke; Ishikawa, Tsuyoshi; Sagawa, Takuya; Ikehara, Minoru; Yamazaki, Toshitsugu (PANGAEA, 2025)
A precise age model of marine sediment core is crucial for environmental studies of the past such as paleoceanography, paleoclimatology, and paleo-hazard studies. Here we report a dataset of oxygen isotope ratios of foraminifera collected from marine sediment cores recovered from the West Caroline Basin in the western equatorial pacific using a piston coring system of R/V Kairei in 2005 (KR05-15 PC01/PL01, 0.10°S 139.58°E, 3,226 m below sea level). The core depth 4.91–6.25 meters of 12.46-meter-long piston core (PC01), which corresponds to termination 2 (ca. 140–120 kyr ago), and a whole 0.53-m-long pilot core (PL01) were used for the measurement of oxygen isotopes of both planktonic (Globigerinoides ruber, Trilobus sacculifer) and benthic (Uvigerina spp.) foraminifera shells. The already published other datasets of oxygen isotopes of both planktonic and benthic foraminifera shells that were collected from the same sediment core (KR05-15 PC01) are also compiled.
Keywords: Foraminifera; G. ruber; oxygen isotope; Sediment core; Uvigerina spp.; western equatorial Pacific